Anatomy of the antennal dorsal organ in female of Neodryinus typhlocybae (Hymenoptera: Dryinidae): A peculiar sensory structure possibly involved in perception of host vibration. (13th October 2015) - Riolo, Paola; Isidoro, Nunzio; Ruschioni, Sara; Minuz, Roxana L.; Bin, Ferdinando; Romani, Roberto
ABSTRACT: Neodryinus typhlocybae (Hymenoptera: Dryinidae) is a natural enemy of the planthopper Metcalfa pruinosa, which was introduced from North America into Europe and has become established in various regions as a pest species. Vibrational signals play a crucial role in the communication of M . pruinosa, which appears to be exploited by N . typhlocybae . Scanning and transmission electron microscopy have shown that the antennae of N . typhlocybae females have peculiar and complex sensory structures: deep longitudinal grooves that house long sensilla trichodea, termed here "Antennal Dorsal Organs." Such structures were not present on male antennae. These sensilla extend for the length of the grooves, without contact with the groove cuticle. Their hair shaft is empty and aporous, and inserted into a specialized socket, underneath which there is a cuticular ampulla‐like chamber. Each sensillum is associated with two sensory neurons: one terminates at the proximal end of the dendritic sheath; the other continues into the sensillum sinus and is enclosed in the dendritic sheath. This second sensory neuron then enters the ampulla‐like chamber through the circular opening, and then terminates with a conspicuous tubular body at the shaft base. The possible involvement of this peculiar structure in the context of host recognition mechanism is discussed. J. Morphol. 277:128–137, 2016. © 2015 Wiley Periodicals, Inc.